Single- or Pair-Housed: Which Is Better for Captive Southern Tamanduas?. Issue 3 (3rd July 2019) - Catapani, Mariana Labão; Pires, José Salatiel Rodrigues; Vasconcellos, Angélica da Silva
ABSTRACT: The captive environment can limit some important behavioral options for nonhuman animals, which often results in decreased welfare. The companion of a conspecific can be a source of complexity in captivity, but this aspect has received little attention for solitary species. This study investigated the effects of two different housing conditions on the behavior of a solitary species, the Southern tamandua ( Tamandua tetradactyla ). Six individuals housed singly and four housed in pairs in two Brazilian zoological institutions were observed for 10 days from 09:00h to 17:00h during the rainy season. Each individual was observed for 26:40 hours. Compared with singly housed tamanduas, paired animals were less inactive (single = 74.62 ± 5.2%, paired = 28.51 ± 0.04% of the records), foraged and explored more (single = 11.07 ± 3.0%, paired 31.48 ± 0.01% of the records), and exhibited a diversity of behaviors 102.56% greater than single tamanduas. These results suggest that interactions with conspecifics in captivity, even for solitary animals, can promote the performance of desirable behaviors, which in several species has been correlated with improved welfare.